Risk factor, diagnosis, and current treatment of H. pylori Infection in Indonesia: A Literature Review - Rizani Putri Iman; Tiroy Junita; Rinaldo Indra Rachman; Ari Fahrial Syam (Acta Medica Indonesiana, 2021)
Helicobacter pylori (H. pylori) infection has become an emerging problem in Indonesia despite its relatively low prevalence as opposed to other Southeast Asian and Asian countries. Strains containing less virulent genotypes predominantly found in Indonesia is suggested to be the rationale for why the disease prevalence, as well as its gastric cancer complication, remain inferior in respect of neighboring counterparts. Although endoscopic evaluation is still necessary to determine the gastric mucosal status of those infected with H. pylori, the infection itself can be easily diagnosed with test-and-treat strategy especially in areas with limited resources. Several findings revealed high rates of antibiotic resistance varying among Indonesian regions and ethnicities, suggesting that triple therapy regimen may not be suitable for all population. Whereas treatment should be based on the pattern of resistance in respected region, novel regimens involving furazolidone, rifabutin, and sitafloxacin are proposed as potential drugs of choice to eradicate H. pylori infection. In order to determine the adequate approach for H. pylori infection in Indonesia, further multicenter studies involving larger sample size should be conducted.